Evaluasi Kinerja Pelayanan Terminal Tipe C Belik di Kabupaten Pemalang sebagai Upaya Peningkatan Layanan Transportasi Publik - Difanda Arjun Navia; Destria Rahmita; Nurul Fitriani; Setia Hadi Pramudi (Jurnal Civil Engineering Study, 2025)
This research aims to evaluate the performance of Type C Terminal Belik in Pemalang Regency and to formulate improvement strategies. The methods used include user surveys, field observations, and interviews, complemented by an analysis of the Customer Satisfaction Index (CSI) and SWOT. The survey results from 100 respondents indicate that the majority of users are productive-age males working in the informal and private sectors. The CSI value of 59.25% indicates that users' satisfaction is in the 'fairly satisfied' category. The inventory of services shows that although most basic facilities such as waiting rooms, parking areas, and breastfeeding rooms are available, there are still shortcomings in safety, cleanliness, as well as information and complaint media. SWOT analysis produces improvement strategies that include optimizing infrastructure, enhancing human resource capacity, utilizing information technology, and cross-sector partnerships. This research shows that improving the overall and sustainable quality of terminal services is essential to realize terminals as safe, comfortable, and efficient public transportation hubs. Recommendations are provided so that terminal managers can use the results of this evaluation as a basis for service improvement in accordance with the standards set by the government.